2011
DOI: 10.1017/s1049023x11000380
|View full text |Cite
|
Sign up to set email alerts
|

(A24) Does Community Emergency Care Initiative Improves the Knowledge, Skill And Attitude of Healthcare Workers and Laypersons in Basic Emergency Care in India?

Abstract: Prehospital and Disaster Medicinethe administration of IV f luids, antibiotics, and analgesia. Radiographs of specific sites and trauma series were used to rule out bone injuries. There was lack of documentation in most of the medical charts. Conclusions: The emergency department was overwhelmed with the number of patients that it received. Therefore, an updated disaster plan and regular disaster drills are required. Rapid and accurate triage could minimize mortality among bombing survivors significantly. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The authors have taken initiatives in this regard, and the All India Institute of Medical Sciences BEC course was designed to address the issue. [ 5 ] They have trained medical and nonmedical personnel, including paramedics, police, and paramilitary forces in BEC. Allison et al .…”
Section: Discussionmentioning
confidence: 99%
“…The authors have taken initiatives in this regard, and the All India Institute of Medical Sciences BEC course was designed to address the issue. [ 5 ] They have trained medical and nonmedical personnel, including paramedics, police, and paramilitary forces in BEC. Allison et al .…”
Section: Discussionmentioning
confidence: 99%
“…To assess the validity, we did a pilot study on police personal and found a good improvement in the knowledge about basic emergency care and CPR. [ 4 ]…”
Section: Methodsmentioning
confidence: 99%